A multiscale experimentally-based finite element model to predict microstructure and damage evolution in martensitic steels. (April 2021) - Meade, Edward D.; Sun, Fengwei; Tiernan, Peter; O'Dowd, Noel P.
Abstract: The objective of this work is to investigate the plastic deformation and associated microstructural evolution and damage in a martensitic steel at multiple length scales, using a combination of finite-element (FE) modelling and experimental measurements. A multiscale model is developed to predict damage evolution in the necked region of a uniaxial tensile test specimen. At the macroscale, a von Mises plasticity FE model in conjunction with a Gurson-Tvergaard-Needleman damage model is used to predict the global deformation and damage evolution. A physically-based crystal plasticity model, incorporating a damage variable is used to investigate the microscale plastic deformation behaviour and the changes in crystal orientation under large strains. The model predicts that slip bands form at the onset of plastic deformation and rotate to become almost parallel to the loading direction at large strain. In the necked region, the initially randomly orientated microstructure develops texture, brought about by inelastic deformation and lattice rotation towards the stable [011] orientation. The predicted crystal orientations and misorientation distribution are in good agreement with measurements obtained through electron backscatter diffraction in the centre of the necked region of the tensile test specimens. The experimental and modelling techniques developed in this work can be used to provide information on the evolution of plastic deformation and damage as well as the orientation-dependent crack initiation and microstructural evolution during large deformation of engineering materials. Highlights: Microstructure and damage evolution of a martensitic steel have been analysed using a multiscale finite element model. The model has been validated experimentally over multiple length scales using multiple techniques. The model predicts crystal orientation consistent theoretical predictions of orientation change under uniaxial loading. Large plastic deformations can lead to generation or annihilation of high angle grain boundaries.